Prenatal multi-metal exposure and offspring health - Zhou Yexinyi; Jin Lanfei; Chen Guangdi (生物医学转化)
In recent years, the effects of prenatal metal exposure on offspring health have attracted widespread attention. The fetal period is a sensitive window for exposure to environmental pollutants, during which even low-dose metal exposure may disrupt normal growth and development, with potential health consequences extending from childhood into adulthood. Recent research has highlighted the crucial role of the placenta in mediating the relationship between metal exposure and offspring health. In real-world exposure scenarios, pregnant women are often exposed to multiple metals simultaneously. This review aims to systematically summarize current epidemiological research on the association between prenatal multi-metal exposure and offspring health and to explore the potential biological mechanisms involving the placenta in this process.